The Linguistic Landscape of Accommodations in Ubud - Ni Made Ariani; Ni Luh Putu Krisnawati (PAROLE: Journal of Linguistics and Education, 2022)
This research investigates what languages signs in the accommodation businesses use in the area of Ubud, Bali, Indonesia to introduce or promote their businesses. As it is widely known, Ubud has become one of the most visited destinations in the world. The blooming tourism industry in Ubud provides an important effect in the growth of this business. Analyzing the linguistic situation of this region is expected to provide an important insight about the position of Balinese as the local language, Indonesian as the national language and English as the international language. The finding of this research shows that among the entire 328 collected signs in this research, Balinese is used as many as 266 times in bilingual signs, Indonesian is used as many as 258 times in bilingual signs, English is used as many as 373 times, both in monolingual and bilingual signs. This finding shows that English still dominates the communication system in this area, therefore Balinese and Indonesian need to promoted more in public space.